Anticoagulant therapy in a hemodialysis patient at high risk of thrombotic and hemorrhagic complications. Case report - Saida A. Orudzheva; Anton N. Kudryavtsev; Valentina S. Demidova; Alexandr A. Ushakov; Samera D. Magomedova; Valery A. Mitish; Alexey V. Kuprin; Elena I. Bozheva (ZAO "Consilium Medicum", 2023)
An attempt to preserve the knee joint in a patient on hemodialysis with stage IV lower limb ischemia with a high risk of thrombotic and hemorrhagic complications is presented. Multifocal atherosclerosis and extensive occlusion of the arteries of the lower leg ruled out the technical possibility of revascularization. The patient refused the proposed hip amputation. An attempt was made to perform amputation at the level of the lower leg. Required therapy aimed at the treatment and prevention of thrombotic complications, and optimization of microcirculation in the ischemic limb. For this purpose, a prolonged blockade of the sciatic and femoral nerves, combined anticoagulant therapy, and treatment with alprostadil were performed. Therapy with antithrombotic and vasoactive drugs was not effective and was complicated by the state of persistent hypocoagulation with an episode of bleeding. Amputation of the limb at the level of the thigh was performed according to vital indications after correction of hypocoagulation. The lack of clinical recommendations on anticoagulant therapy for critical lower limb ischemia in patients with stage 5 chronic kidney disease requires an individual approach to the choice of antithrombotic drugs and their doses, monitoring the state of blood coagulation using an integral method for assessing the hemostasis system thromboelastography.